If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) + -4 = 0 Reorder the terms: 2(-5 + x) + -4 = 0 (-5 * 2 + x * 2) + -4 = 0 (-10 + 2x) + -4 = 0 Reorder the terms: -10 + -4 + 2x = 0 Combine like terms: -10 + -4 = -14 -14 + 2x = 0 Solving -14 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = 0 + 14 2x = 0 + 14 Combine like terms: 0 + 14 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| -6(x+1)-11=32+5 | | 9-2x=x-27 | | ln(x+11)-ln(x-3)=ln(3) | | 7(5c-1)-8=33c+7 | | 2x^4-4x^3-x^2+2x=gcf | | -24=21x | | -3x+5=-31-7x | | 3x+9=10y+8 | | 5z^3+15z^2+3z+9= | | 16x+4y=7 | | -56-2x=5x+7 | | 2x+-6+-4x+9=5x | | x(x+13)=x+10(x+1) | | y/5-9=-2 | | 6=12s-6/5 | | 1=.5x-1 | | 2x-6-4x+9=5 | | w/2+14=12 | | x-1/2=5/6 | | 5y+26=y+10 | | (v^2-3v-40)/(v+3) | | 17=7-(y+8) | | 8.1x^6+6.3x^5-4.5x^2+3.6x= | | 3(x+6)+2(x-2)=6x | | 34-6x=5 | | 6+y=-44 | | (v+3)/(v^2-3v-40) | | 5y+6y=y+10 | | 5/3x+3+23 | | 4.5+x=0.5 | | 6(-8)+y=-44 | | 3(x+6)+2(x-2)=6 |